(untitled) (Cardiovascular Journal, 2021)
Background: Red cell distribution width is a simple measure of red cell size heterogeneity (i.e., anisocytosis) in peripheral blood measured by hematology auto analyzer and has been shown to be a predictor of poor outcomes in various cardiovascular conditions including coronary artery disease (CAD). The present study was intended to find the association between RDW-CV and severity of CAD in NSTEMI patients. Methods: The present cross-sectional analytical study was carried out in the Department of Cardiology, National Institute of Cardiovascular Diseases (NICVD), Dhaka, Bangladesh, from June 2018 to July 2019. A total of 70 NSTEMI patients undergoing coronary angiogram during the index hospitalization were included in the study. They were divided into two groups on the basis of RDW-CV (Group-I RDW-CV <14.3%; Group-II RDW-CV ≥14.3%). Severity of coronary artery disease was determined by SYNTAX score and correlation between RDW-CV and SYNTAX score was assessed. Results: SYNTAX score was significantly higher in patients with RDW-CV ≥14.3% than that in patients with RDW-CV <14.3% (24.51±9.76 vs. 13.5±7.71, p<0.0001). The risk of having severe CAD in patients with RDW-CV ≥14.3%was 3.844(95% CI = 1.429-10.340) (p <0.008) times higher in terms of SYNTAX score. A significant positive correlation between RDW-CV and SYNTAX score was noted (r = 0.681, p value < 0.0001). Conclusion: It may be concluded that RDW-CV was significantly associated with the severity of coronary artery disease in NSTEMI patients and it may be considered as an independent predictor of severity of CAD. It is easy to assess and inexpensive. So, before performing coronary angiography, it appears to be additive to conventional risk factors and commonly used biomarkers for risk stratification. Cardiovasc j 2021; 14(1): 12-19